Taking stock of the Trinitarian renaissance: What have we learnt? - Venter, Rian (HTS teologiese studies, 2019)
The re-appreciation of the Trinitarian confession in the twentieth century is widely considered a major theological development. Recently, several critical voices emerged, questioning the direction of these explorations. As response, the article identifies major emphases of this rediscovery, namely, the return to sources, the clarification of the function of the confession and its re-envisioning of the nature of divinity, the more centring of the Christian vision in one material principle, the heuristic potential for practical questions and the need for apophatism. The article appreciatively intimates the subtler dynamics to the enthusiasm for the Trinity and briefly highlights the presence of transcendence, narrativity, imagination, analogy and spirituality in the discourse. Some suggestions have been provided for future reflection.